1994
DOI: 10.1002/ar.1092400409
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical detection of actin and 53 kDa polypeptide in the epididymal spermatozoa of rat and mouse

Abstract: Intense labeling of actin in the SDS-extracted rat and mouse spermatozoa was presumably due to the generated demasking of actin epitopes embedded in the perinuclear cytoplasm. The results are important in confirming that actin in the rat and mouse sperm head is not lost during spermiogenesis but apparently contributes to the three-dimensional packing of the mature perinuclear cytoplasm. This study further demonstrates the importance of the methods used in sample preparation and advantages of confocal microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…This clear redistribution of F-actin in the post-acrosomal region was not seen in rodent sperm, and may be due to the fact that samples of rodent sperm were obtained from the epididymis. Nevertheless, in agreement with the studies of Brener et al (2003) and Paranko et al (1994), the post-acrosomal region in control sperm showed the presence of F-actin, and this was in contrast to Howes et al (2001). The polymeric form of actin (F-actin) is thought to be particularly important as its depolymerization between the outer acrosomal and plasma membrane is correlated with initiation of the AR in studies on guinea pig (Breitbart & Spungin 1997) and on bull, ram, mouse and human sperm (Brener et al 2003).…”
Section: Discussionsupporting
confidence: 90%
“…This clear redistribution of F-actin in the post-acrosomal region was not seen in rodent sperm, and may be due to the fact that samples of rodent sperm were obtained from the epididymis. Nevertheless, in agreement with the studies of Brener et al (2003) and Paranko et al (1994), the post-acrosomal region in control sperm showed the presence of F-actin, and this was in contrast to Howes et al (2001). The polymeric form of actin (F-actin) is thought to be particularly important as its depolymerization between the outer acrosomal and plasma membrane is correlated with initiation of the AR in studies on guinea pig (Breitbart & Spungin 1997) and on bull, ram, mouse and human sperm (Brener et al 2003).…”
Section: Discussionsupporting
confidence: 90%
“…Prior to the acrosome reaction, F actin undergoes depolymerization. Actin is also detected in the outer dense fibers of the sperm tail, suggesting that actin may regulate sperm motility (3,13,29). We postulate that altered expression of Fscn1 contributes to reduced sperm motility and folding of sperm tails in Taf7l Ϫ/Y testes.…”
Section: Discussionmentioning
confidence: 77%
“…To avoid saturation of PCR, products were taken after various cycles (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and analyzed by gel electrophoresis. One microgram of total RNA from adult wildtype and XX Y‫ء‬ testes was used for reverse transcription.…”
Section: Quantitative and Semiquantitative Reverse Transcription (Rt)mentioning
confidence: 99%
“…The presence of actin in mammalian spermatozoa has been demonstrated in several species including cattle, boar, rat, mouse, guinea pig, hamster, mole, human, rabbit, fat tailed dunnart and opossum (Flaherty et al 1986 ;Halenda et al 1987 ;Olson & Winfrey, 1991 ;Castellani-Ceresa et al 1992 ;MorenoFierros et al 1992 ;Breed et al 1993 ;Paranko et al 1994). However, the precise localisation of this protein has not been conclusively demonstrated (Lora-Lamia et al 1986 ;Paranko et al 1994 ;Yagi & Paranko, 1995).…”
mentioning
confidence: 99%
“…However, the precise localisation of this protein has not been conclusively demonstrated (Lora-Lamia et al 1986 ;Paranko et al 1994 ;Yagi & Paranko, 1995). In the prepubertal testis, F-actin is uniformly distributed throughout the cytoplasm of the undifferentiated spermatid.…”
mentioning
confidence: 99%